ПАРТІЙНО0РАДЯНСЬКА НОМЕНКЛАТУРА В УКРАЇНІ, 194501948 РР.: ДЕЯКІ АСПЕКТИ ПРОБЛЕМИ (Zaporizhzhia Historical Review, 2021)
In the given article characteristics of the process of forming of party and soviet high-level officials after the World War 2 are analyzed. Objective and subjective conditions in training, selection and structuring of leading party and soviet workers are considered. Additional attention is paid to new tendencies of work with bureaucracy. Specific character of functioning party institutions after the war is also examined.